2006
DOI: 10.1007/s00404-006-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postpartum counseling on postpartum contraceptive use

Abstract: Introduction The postpartum period is one of the important transitional phases in women's life (1). Following serious changes of delivery and transition to parenthood, primigravidas undergo significant physical, social and psychological changes (2). With important physiological and psychological changes such as adapting to changes in the body, woman face maternal role and support of certain people (3). Therefore, mother needs to adapt to new life and newborn care (4). Most of them aren't ready to take care of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 10 publications
4
24
2
1
Order By: Relevance
“…The variation in postpartum contraceptive practices seen in this study confirmed previous studies [6,7,8,9]. The variety of contraceptive methods used is related to various differences in baseline characteristics, details of intended fertility spacing, completeness of the family, and attitude and beliefs of either the women or care providers in individual institution.…”
Section: Discussionsupporting
confidence: 77%
“…The variation in postpartum contraceptive practices seen in this study confirmed previous studies [6,7,8,9]. The variety of contraceptive methods used is related to various differences in baseline characteristics, details of intended fertility spacing, completeness of the family, and attitude and beliefs of either the women or care providers in individual institution.…”
Section: Discussionsupporting
confidence: 77%
“…6 Postpartum education and counselling has been reported to increase contraception usage, 7 but also to have no impact on the use of effective and modern postpartum contraception. 5 A meta-analysis regarding the effectiveness of postpartum education on contraceptive use concluded that postpartum education led to more contraceptive use and fewer unplanned pregnancies. 8 In Mexico, where family planning counselling is integrated into routine prenatal care, women are twice as likely to use postpartum contraception, 9 with condom use, IUD and sterilization increasing significantly with prenatal family planning counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum contraceptive counselling has been studied by several groups, but the prenatal period is usually neglected. 4,5 Contraceptive counselling, given according to the needs of couples during routine prenatal care visits, especially in the third trimester, might increase the use of postpartum contraception.…”
Section: Introductionmentioning
confidence: 99%
“…38,40 The effectiveness of counseling interventions in reducing unintended pregnancy and increasing postpartum contraceptive use, however, has been seldom examined. 39,43 Of those studies investigating the topic, several have concluded that focused contraceptive counseling in the postpartum or antepartum period is effective, [45][46][47] yet others report no impact on contraceptive use following contraception counseling 48 alone, versus educational leaflets, 49 or a short-term increase in contraceptive use only. 40 A systematic review (2010) of contraceptive counseling interventions taking place in the postpartum period, including both short-term and multiplecontact interventions, concluded that postpartum contraceptive education led to more contraception use and fewer unplanned pregnancies, though, was based on a limited number of studies.…”
Section: Postpartum Contraception Education For Patients; When To Stamentioning
confidence: 99%
“…41 Several small studies have investigated the way in which postpartum contraception is approached in an attempt to determine which method may be most effective. 38,[46][47][48]50 For example, women who watched a video were less satisfied than those who had received counseling from a physician, though the video watchers were as likely to be satisfied as those who received a pamphlet. 43 In a paper investigating patient satisfaction and the impact of written material about postpartum contraceptive decisions in 109 women, women in the intervention group were more likely to state that written material contributed to their ultimate choice in birth control.…”
Section: Postpartum Contraception Education For Patients; When To Stamentioning
confidence: 99%